Pengembangan Desa Berdaya Bebas Covid-19 melalui Pendekatan Holistic - Sutarmi Sutarmi; Tavip Indrayana; Marlynda Happy Nurmalita Sari (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
The spread of Covid-19 cannot be stopped, but people must start adapting to new life habits or “New Normal Life”. This activity aims to increase knowledge and empower the community in adapting to a new life during the Covid-19 pandemic. Target residents of Temurejo Village, Blora. Methods include preparation, organizing, education and training, self-empowerment and integration, implementation and termination. The activity begins with coordination, preparation, determining the territory and schedule of activities. Followed by organizing, coordinating with the head of Temurejo Village, community representatives and the Covid -19 cluster. Education and training to increase public knowledge and understanding of health protocols and self-empowerment during a pandemic. Empowerment and integration by exploring the potential of the community which is integrated with the urgent need in the pandemic era, namely the manufacture of handwashing with the stepping method. Implementation by handing over hand-washing tools and disinfectants, demonstrations of washing hands and spraying public places. The final stage is monitoring evaluation and activity reporting. Activities carried out in accordance with the targets and activity plans. The potential of adequate human resources in receiving science and technology, health protocol procedures and assistance in making hand washing equipment using the stepping method can be developed into a productive effort to become a UMKM in the era of new normal life.It is hoped that there will be similar activities that are regularly scheduled to maintain a healthy lifestyle and develop community potential-based UMKM formation activities.